(untitled) (Development Service Industry Management, 2025)
The article highlights modern approaches to corporate management, according to which the organizational structure should be adaptive, transparent and aimed at increasing efficiency. It is emphasized that the corporate management structure is one of the main elements that determine the success and efficiency of the enterprise’s functioning in modern conditions of significant unpredictability and increased risks and threats. This management model provides a clear distribution of roles, responsibilities and powers among different levels of the management hierarchy, which allows organizing the work of the enterprise in such a way as to achieve strategic goals and adapt to changes that are constantly occurring in the external and internal environment. The basic methodological principles of the formation of the organizational structure of corporate management are summarized, which cover the following processes: determination of the purpose, goals and tasks of corporate management; choosing the type of organizational structure of corporate management; formation of key units of corporate management; distribution of powers and responsibilities of corporate management bodies; implementation of communication and control mechanisms in the corporate management system; adaptation of the corporate management system to changes in the external environment. A properly constructed organizational structure of corporate governance not only contributes to the achievement of strategic goals, but also increases the company’s competitiveness, ensuring its sustainability and efficiency in the long term. A properly constructed corporate management structure enables various divisions of the enterprise to interact harmoniously, ensuring effective coordination of actions, minimizing conflicts between departments, and optimizing the use of resources. Moreover, under such a vector of modernization of the management system, enterprises are able to quickly respond to changes in market conditions, introduce new technologies and implement innovations, as well as ensure a stable increase in competitiveness.